Prehospital intravenous access for survival from out-of-hospital cardiac arrest: propensity score matched analyses from a population-based cohort study in Osaka, Japan - Fujii, Tomoko (BMJ Open, 2017)
OBJECTIVES: Prehospital intravenous access is a common intervention for patients with out-of-hospital cardiac arrest (OHCA). We aimed to assess the effectiveness of prehospital intravenous access and subsequent epinephrine administration on outcomes among OHCA patients. METHODS: We conducted a prospective cohort study of patients with OHCA from non-traumatic causes aged ≥18 years in Osaka, Japan from January 2005 through December 2012. The primary outcome was 1-month survival with favourable neurological outcome defined as a cerebral performance category of 1 or 2. The association between intravenous line placement and survival with favourable neurological outcome was evaluated by logistic regression, after propensity score matching for the intravenous access attempt stratified by initial documented rhythm of ventricular fibrillation (VF) or non-VF. The contribution of epinephrine administration to the outcome was also explored. RESULTS: Among OHCA patients during the study period, 3208 VF patients and 38 175 non-VF patients were included in our analysis. Intravenous access attempt was negatively associated with 1-month survival with a favourable neurological outcome in VF group (OR 0.76, 95% CI 0.59 to 0.98), while no association was observed in the non-VF group (OR 1.06, 95% CI 0.84 to 1.34). Epinephrine administration had no positive association in the VF patients (OR 0.75, 95% CI 0.51 to 1.07) and positively associated in the non-VF patients (OR 1.52, 95% CI 1.08 to 2.08) with the favourable neurological outcome. CONCLUSIONS: Intravenous access attempt could be negatively associated with survival with a favourable neurological outcome after OHCA. Subsequent epinephrine administration might be effective for non-VF OHCAs.